2010
DOI: 10.1203/pdr.0b013e3181cde843
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Hypoxic Newborn Piglets With Supplementary Oxygen Induces Dose-Dependent Increase in Matrix Metalloproteinase-Activity and Down-Regulates Vital Genes

Abstract: ABSTRACT:The optimal oxygen concentration for newborn resuscitation is still discussed. Oxygen administration during reoxygenation may induce short-and long-term pathologic changes via oxidative stress and has been associated to later childhood cancer. The aim was to study changes in oxidative stress-associated markers in liver and lung tissue of newborn pigs after acute hypoxia followed by reoxygenation for 30 min with 21, 40, or 100% oxygen compared with room air or to ventilation with 100% oxygen without pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…In our newborn hypoxia-reoxygenation piglet model, matrix metalloproteinases (MMP) 2 and 9 were measured to assess oxidative tissue damage and repair in lung, liver, heart and brain. Resuscitation with 100% oxygen gave significantly higher values compared with ambient air [34,35,37,38]. Studies in newborn lambs also showed more injury to the brain when resuscitation was carried out with 100% oxygen compared with air [39].…”
Section: Hyperoxic Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…In our newborn hypoxia-reoxygenation piglet model, matrix metalloproteinases (MMP) 2 and 9 were measured to assess oxidative tissue damage and repair in lung, liver, heart and brain. Resuscitation with 100% oxygen gave significantly higher values compared with ambient air [34,35,37,38]. Studies in newborn lambs also showed more injury to the brain when resuscitation was carried out with 100% oxygen compared with air [39].…”
Section: Hyperoxic Injurymentioning
confidence: 99%
“…Using different oxygen concentrations for newborn resuscitation in a newborn piglet model, we found a clear dose-dependent oxygen toxicity [35,38,40] as shown in figure 2. In brain tissue, the most prominent changes occurred in neuronal populations in a dose-response manner.…”
Section: Hyperoxic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Subsequent experimental studies and clinical studies by Max Vento and his group and others have been extremely important, as these studies presented evidence that it is actually harmful to resuscitate newborn babies with 100% oxygen. [20][21][22][23][24][25][26] The Resair 2 study was criticized mainly for two reasons. First, the study was not strictly randomized nor was it blinded.…”
Section: Discovery Through a Failurementioning
confidence: 99%
“…This is in agreement with the findings of numerous animal experiments showing that a brief exposure of oxygen following hypoxia has dramatic deleterious effects on the newborn brain. 20,21,24,25 It has been shown that the first breath is delayed by 30 s in babies resuscitated with 100% compared with those resuscitated with 21% oxygen. Heart rate at 90 s and the 5-m Apgar score were also lower when 100% oxygen was applied.…”
Section: Discovery Through a Failurementioning
confidence: 99%